Information Asymmetry and Financial Dollarization in Sub-Saharan Africa - Simplice Asongu; Ibrahim D. Raheem; Vanessa S. Tchamyou (African Governance and Development Institute (AGDI), 2016)
Financial dollarization in Sub-Saharan Africa is the most persistent compared to other regions of the world. This study complements the existing scant literature on dollarization in Africa by assessing the role of information sharing offices (public credit registries and private credit bureaus) on financial dollarization in 26 countries of SSA for the period 2001-2012. The empirical evidence is based on Ordinary Least Squares (OLS) and Generalised Method of Moments (GMM). The findings show that information sharing offices (which are designed to reduce information asymmetry) in the banking industry are a deterrent to dollarization. Policy implications are discussed.
Keywords: E31; E41; G20; O16; O55; 330; Dollarization; Openness; Information Asymmetry; Africa